1993
DOI: 10.1136/jnnp.56.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Age influences magnitude but not duration of response to levodopa.

Abstract: Following an all-night fast, 45 patients with Parkinson's disease were examined using certain motor (J Neurol Neurosurg Psychiatry 1993;56:65-68)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 23 publications
4
21
0
Order By: Relevance
“…Thirdly, after withdrawal from levodopa motor functions may fluctuate so that it may be difficult to assess baseline motor scores (Nutt et al, 1988). In agreement with previous studies, the residual motor scores increased with age and age at disease onset (Table 1) (Godwin-Austen et al, 1971;Danielczyk et al, 1980;Goetz et al, 1988;Blin et al, 1991;Durso et al, 1993). This finding is also in accordance with a study demonstration an age-related increase in global parkinsonian disability (Diamond et al, 1989).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thirdly, after withdrawal from levodopa motor functions may fluctuate so that it may be difficult to assess baseline motor scores (Nutt et al, 1988). In agreement with previous studies, the residual motor scores increased with age and age at disease onset (Table 1) (Godwin-Austen et al, 1971;Danielczyk et al, 1980;Goetz et al, 1988;Blin et al, 1991;Durso et al, 1993). This finding is also in accordance with a study demonstration an age-related increase in global parkinsonian disability (Diamond et al, 1989).…”
Section: Discussionsupporting
confidence: 88%
“…Studies in patients with onset of the disease before the age of 65 years revealed a stable course of the residual scores for tremor, rigidity, and rapid hand and foot movements during 10 to 20 years of levodopa therapy, whereas axial motor functions aggravated progressively (Klawans, 1986;Bonnet et al, 1987). Previous studies suggest decreasing responsiveness of parkinsonian motor symptoms to levodopa with advancing age (Blin et al, 1991;Durso et al, 1993). Therefore, the effect of disease duration on the expression of residual motor symptoms might be related to age.…”
Section: Introductionmentioning
confidence: 86%
“…The hypothesis that the main impact of age at onset on the progression of the degenerative process occurs in the early to mid stages of the disease is further supported by a recent clinicopathological study 5. On the other hand, however, our data in patients with a history of 10–20 years of disease confirmed only a higher likelihood of developing motor complications (motor fluctuations and levodopa-induced dyskinesias) in patients with younger-onset PD 10 24 25. Taken as a whole, these data suggest a differential age-related rate of progression only in the short term, while these factors are likely to have an additive effect on the natural history of PD in the long term 12 26.…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, as life expectancy is still increasing, future predictions of incidence and prevalence data should probably take into account the observed time trends in age at onset. In this respect, there are also potential implications for medical care policies as previous studies have shown a more rapid rate of progression [20,21] and a lower magnitude of response to levodopa [22,23] in patients with more advanced age at onset.…”
Section: Discussionmentioning
confidence: 93%